Standar Ganda dalam Ujaran Kebencian terhadap Artis K-Pop: Kajian Pragmatik - Rika, Atta; Br. Perangin-angin, Alemina; Fitria, Dila (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2024)
This study aims to describe the forms of double standards in hate comments against K-POP artists found on Instagram. This research utilized a descriptive qualitative approach, which refers to research methods that produce descriptive data using pragmatics approach. The data were collected from the most followed K-POP pages on Instagram in Indonesia: @fyi.korea, @officialkvibes, and @coppamagz. The objects of this study include hate comments found on these Instagram pages. Based on the results of observations on these pages, it was found that some of the data included hate comments aimed at several K-Pop idols. The results of the study indicate that the topics that receive the most hate comments are related to dating scandals, the sexy appearance of K-POP artists, and also the physical appearance and visual aspects. Based on the result, the double standards towards the involved K-POP artists are glaringly evident. It can be concluded that there are two major factors contributing to these double standards: gender and popularity. In terms of gender, female K-POP artists are more frequently criticized and receive hate comments compared to their male counterparts. Meanwhile, in terms of popularity, K-POP artists with higher popularity levels tend to receive hate comments more often than those who are not as popular. Keyword : Hate comments, Double standard, K-POP Artist, Pragmatics